Assistance in Making Halal Certificates for Apem Putih MSMEs Kadubungbang Village, Pandeglang - Sari, Titis Nistia; Abduh, Muhammad; Saputra, Galih Ginanjar (EQUATOR SINAR AKADEMIA, 2024)
Kadubungbang Village, Pandeglang has MSME business actors in the form of special foods, one of which is white apem. Halal certification socialization and assistance activities were carried out in Kadubungbang Village, Cimanuk District, Pandeglang Regency, Banten Province. The stages carried out include Making NPWB and NIB, Account registration in the SIHALAL application, Filling in data guided by PPH companions, Submitting a Halal Certificate Application. This activity can only be carried out until the submission of a halal certificate, due to time limitations and also the next process takes a long time.